The Level of Persistence in Completing Tasks Based on The Student's Potential - Safari, NFN (Indonesian Journal of Educational Assessment, 2021)
The main purpose of this study is to find out whether there is a relationship between the level of persistence in completing assignments and students' self-potential. The design used in this study is quantitative research. The data in this study is taken from the 2020 Minimum Competency Assessment (AKM) test for SMA/SMK organized by the Center for Assessment and Learning (Pusmenjar) R&D, MOEC of Indonesia. The population of this study is the condition of the level of enjoyment of high school / vocational students who are studying with teachers at school in 2020, while the sample is the condition of the level of pleasure of senior high school/vocational students who were taking the 2020 AKM test. The data in this study is in the form of a questionnaire answered by 269.988 students from senior high school / vocational school participating in AKM 2020 (514 districts/districts in 34 provinces in Indonesia). Based on the results of simple regression analysis, the following results were obtained; statistically there is a positive relationship between the level of persistence in completing the task and self-potential (P<0.05) although the contribution is relatively small ( 0.14%). The reliability of the instrument is 1.00, higher than the reliability of the person (0.31). The conclusion is that there is a significant relationship between the level of persistence in completing assignments and students' self-potential (P<0.05).